Experimental study on flue gas condensate capture and heat transfer in staggered tube bundle heat exchangers. (August 2018) - Wang, Enlu; Li, Kai; Husnain, Naveed; Li, Deli; Mao, Jinda; Wu, Wei; Yang, Tianwei
Highlights: Effects of factors on condensate capture rate and heat transfer are presented. Compound HT coefficient is 2–4 times the pure convective HT coefficient. Condensate capture rate can reach above 50%. Empirical formula of the heat transfer coefficient is fitted. Abstract: Experiments on the flue gas condensation in multi-row staggered tube bundle heat exchangers are carried out. The effects of the flue gas velocity, water vapor volume fraction, cooling water flow rate, cooling water temperature, and cooling water flow arrangement (series or parallel) on the condensate capture rate and heat transfer coefficient are presented and discussed. The compound heat transfer coefficient can attain a value 2–4 times that of the pure convective heat transfer coefficient, and the condensate capture rate can attain a value above 50%. There is a suitable cooling water flow rate with an adequately low wall temperature and an adequately high heat transfer coefficient and condensate capture rate. However, the condensate capture rates of the heat exchangers in the series arrangement are apparently lower than those in the parallel arrangement. With the increase of the cooling water temperature, the condensate capture rate decreases; however, the heat transfer coefficient increases under a similar condition. Finally, the empirical formula of the heat transfer coefficient of multi-row staggered tube bundle heat exchangers is determined, and it exhibits good agreement with the experimental data.